2018
DOI: 10.1111/bju.14533
|View full text |Cite
|
Sign up to set email alerts
|

Occupation and risk of cancer of the renal pelvis in Nordic countries

Abstract: The study suggests that there is an association between profession and risk of malignancy of the renal pelvis. The possible associations between exposure to asbestos, heavy metals and welding fumes, and risk of developing the disease should be studied further.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 15 publications
0
13
0
Order By: Relevance
“…Seven studies reported on UTUC incidence according to occupation [ 24 , 27 , 48 52 ]. Five of these studies were based on the national cancer registries and censuses of Nordic countries [ 27 , 48 , 50 52 ]. A total of 54 occupational categories are included in the comprehensive study by Michalek and colleagues [ 27 ] on five Nordic countries (Denmark, Iceland, Finland, Norway and Sweden) between 1961 and 2005.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Seven studies reported on UTUC incidence according to occupation [ 24 , 27 , 48 52 ]. Five of these studies were based on the national cancer registries and censuses of Nordic countries [ 27 , 48 , 50 52 ]. A total of 54 occupational categories are included in the comprehensive study by Michalek and colleagues [ 27 ] on five Nordic countries (Denmark, Iceland, Finland, Norway and Sweden) between 1961 and 2005.…”
Section: Resultsmentioning
confidence: 99%
“…Five of these studies were based on the national cancer registries and censuses of Nordic countries [ 27 , 48 , 50 52 ]. A total of 54 occupational categories are included in the comprehensive study by Michalek and colleagues [ 27 ] on five Nordic countries (Denmark, Iceland, Finland, Norway and Sweden) between 1961 and 2005. The occupation categories with the highest SIR were seamen (1.51 [95% CI 1.23–1.82]), printers (1.39 [1.11–1.71]), and welders (1.37 [1.03–1.78]).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Association and risk of occupational exposure for KCa distribution Table 5shows socio demographic distribution as mean age from all studies was 56.45±17.6 and male were majority with average percentage of 95.3% and about 42.5% were smokers. Table 6 and Figure 4 shows association and risk of occupational exposure for renal cancer distribution.Peters et al 20 (OR 1.63, 95% CI: 1.33-1.96), Saint-Jacques et al 22 (OR 1.808, 95% CI: 1.34-2.43) and Michelek et al 23 (OR 1.842, 95% CI: 1.53-2.18) showed significant risk but Michelek et al 23 (OR 0.81, 95% CI: 0.71-1.15 ), Zaitsu et al 19 (OR 1.04,95% CI: 0.96-1.12) and Callahan et al 24 (0.95, 95% CI: 0.84-1.37 ) showed no significant risk or association. After analysis of multiple paper regarding the association between KCa and different occupational exposure we found no significant association (OR 1.04, 95% CI:0.94-1.34).…”
Section: Categorical Meta-analysis Findingsmentioning
confidence: 95%
“…For the studies that investigated the association of occupational exposure and risk of KCa; there were 4 case control studies, 17,20,21,24 3 cohort studies18, 19,23 and 1 ecological study 22 they were all population based studies. For the studies that investigated the association of occupational exposures and risk of bladder cancer; there were 5 case control studies, 26,30,31,34,35 3 cohort studies, 25,28,33 2 cross sectional studies, 27,29 and 1 social perspective.…”
Section: Quality Assessment Of Studiesmentioning
confidence: 99%